Lung Density Analysis Using Quantitative Chest CT for Early Prediction of Chronic Lung Allograft Dysfunction. Issue 12 (December 2019) - Horie, Miho; Levy, Liran; Houbois, Christian; Salazar, Pascal; Saito, Tomohito; Pakkal, Mini; O'Brien, Ciara; Sajja, Shailaja; Brock, Kristy; Yasufuku, Kazuhiro; Keshavjee, Shaf; Paul, Narinder; et al.
Abstract : Background: Chronic lung allograft dysfunction (CLAD) limits long-term survival after lung transplantation (LTx). Early detection or prediction of CLAD can lead to changes in patient management that, in turn, may improve prognosis. The purpose of this study was to investigate the utility of quantitative computed tomography (CT) lung density analysis in early prediction of CLAD. Methods: This retrospective cohort was drawn from all consecutive adult, first LTxs performed between 2006 and 2011. Post-transplant monitoring included scheduled surveillance bronchoscopies with concurrent pulmonary-functions tests and low-dose chest CT. Quantitative density metrics (QDM) derived from CT scans obtained at the time of 10%–19% decline in forced expiratory volume in 1 second (FEV1) were evaluated: 114 bilateral LTx recipients (66 with CLAD and 48 stable) and 23 single LTx recipients (11 with CLAD, 12 stable) were included in the analysis. Results: In both single and double LTx, at the time of 10%–19% drop in FEV1 from baseline, the QDM was higher in patients who developed CLAD within 3 years compared with those patients who remained stable for at least 3.5 years. The area under the receiver operating characteristic curve (AUC) was 0.89 for predicting CLAD in single LTx and 0.63 in bilateral LTx. A multipredictor AUC accounting for FEV1, QDM, presence of consolidation, and ground glass opacities increased the AUC to 0.74 in double LTx. Conclusions: QDM derived from a CT histogram at the time of early drop in FEV1 may allow prediction of CLAD in patients after single or double LTx. Abstract : Supplemental Digital Content is available in the text.